ARTIFICIAL INTELIGENCE DALAM PUBLIC RELATION : PELUANG DAN TANTANGAN DI INDONESIA - Latuheru, Rido; Zeynep Pariama, Wildo Clay (JURNAL BADATI, 2025)
This research examines the application of Artificial Intelligence (AI) technology in Public Relations (PR) practice in Indonesia, focusing on the opportunities and challenges faced. The rapid development of AI opens up new opportunities as well as poses challenges for PR practitioners in the digital era. Through a systematic literature review method, this research analyzed 78 relevant articles from various academic and industry sources. The results identified five main opportunities for AI application in PR in Indonesia: data analysis and insights, content and communication personalization, chatbots and customer service, crisis prediction and management, and PR performance measurement and evaluation. Case studies show an increase in PR campaign effectiveness of up to 40% and an increase in engagement of up to 35% through the use of AI. However, the research also revealed five significant challenges: digital and infrastructure gaps, data security and privacy, ethics and transparency, human resource readiness, and cultural adaptation and change resistance. The survey showed that only 35% of PR practitioners in Indonesia feel ready to adopt AI technology. In conclusion, the application of AI in PR in Indonesia offers great opportunities to improve effectiveness and efficiency, but requires a cautious and strategic approach in the face of existing challenges. Collaboration between practitioners, technology developers, policy makers, and academics is needed to develop an effective and ethical framework for the integration of AI in PR practice in Indonesia.